2021
DOI: 10.5194/wcd-2-233-2021
|View full text |Cite
|
Sign up to set email alerts
|

Representation by two climate models of the dynamical and diabatic processes involved in the development of an explosively deepening cyclone during NAWDEX

Abstract: Abstract. The dynamical and microphysical properties of a well-observed cyclone from the North Atlantic Waveguide and Downstream Impact Experiment (NAWDEX), called the Stalactite cyclone and corresponding to intensive observation period 6, is examined using two atmospheric components (ARPEGE-Climat 6.3 and LMDZ6A) of the global climate models CNRM-CM6-1 and IPSL-CM6A, respectively. The hindcasts are performed in “weather forecast mode”, run at approximately 150–200 km (low resolution, LR) and approximately 50 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…Our approach is based on the case study of an extratropical cyclone that occurred during NAWDEX called the Stalactite cyclone (29 September -3 October 2016) and corresponding to Intensive Observing Period (IOP) 6. It was an explosively deepening cyclone at a rate of roughly 24 hPa in 24 hours (Flack et al, 2021) that formed off the east coast of Newfoundland and travelled over the North Atlantic toward Iceland and Greenland. This large-scale cyclone participated in the formation of a blocking over Scandinavia (Schäfler et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach is based on the case study of an extratropical cyclone that occurred during NAWDEX called the Stalactite cyclone (29 September -3 October 2016) and corresponding to Intensive Observing Period (IOP) 6. It was an explosively deepening cyclone at a rate of roughly 24 hPa in 24 hours (Flack et al, 2021) that formed off the east coast of Newfoundland and travelled over the North Atlantic toward Iceland and Greenland. This large-scale cyclone participated in the formation of a blocking over Scandinavia (Schäfler et al, 2018).…”
mentioning
confidence: 99%
“…Blanchard et al (2020) and Blanchard et al (2021) studied the WCB-embedded convection by performing convection-permitting model simulations while Mazoyer et al (2021) analyzed the impact of cloud microphysics on the WCB activity of the Stalactite cyclone with similar convection-permitting simulations. Flack et al (2021) analyzed the whole life cycle of the cyclone in simulations of two climate models. Maddison et al (2020) showed that mediumrange forecast skills of the cyclone are sensitive to the choice of the deep convection schemes but none of these studies systematically investigated the role of parameterized deep convection on the WCB of the cyclone at short range.…”
mentioning
confidence: 99%
“…Our approach is based on the case study of an extratropical cyclone that occurred during NAWDEX called the Stalactite cyclone (29 September-3 October 2016) and corresponding to Intensive Observing Period (IOP) 6. It was an explosively deepening cyclone at a rate of roughly 24 hPa in 24 h (Flack et al, 2021) that formed off the east coast of Newfoundland and travelled over the North Atlantic toward Iceland and Greenland. This large-scale cyclone participated in the formation of a block over Scandinavia (Schäfler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Blanchard et al (2020) and Blanchard et al (2021) studied the WCB-embedded convection by performing convection-permitting model simulations, while Mazoyer et al (2021) analysed the impact of cloud microphysics on the WCB activity of the Stalactite cyclone with similar convection-permitting simulations. Flack et al (2021) analysed the whole life cycle of the cyclone in simulations of two climate models. Maddison et al (2020) showed that medium-range forecast skills of the cyclone are sensitive to the choice of the deep convection schemes, but none of these studies systematically investigated the role of parameterized deep convection on the WCB of the cyclone at short range.…”
Section: Introductionmentioning
confidence: 99%
“…The extratropical cyclone hereafter studied, called the "Stalactite cyclone" (1-4 October 2016), is of particular interest in a number of respects. It was formed off the Newfoundland coast and intensified over the North Atlantic with a deepening rate of 24 hPa in 24 h (Flack et al, 2021) as a classical bomb event (Sanders and Gyakum, 1980). It has been intensively observed during NAWDEX (Schäfler et al, 2018) by three flights: two flights of the French Falcon 20 from the Service des Avions Français Instrumentés pour la Recherche en Environnement (SAFIRE) and one flight from the Deutsches Zentrum für Luft-und Raumfahrt (DLR) Dassault Falcon.…”
Section: Introductionmentioning
confidence: 99%